The Levy Institute Measure of Economic Well-Being, Great Britain, 1995 and 2005 - Selçuk Eren; Thomas Masterson; Edward Wolff; Ajit Zacharias (Levy Economics Institute of Bard College, 2011)
We construct estimates of the Levy Institute Measure of Economic Well-Being for Great Britain for the years 1995 and 2005. We also produce estimates of the official British measures HBAI (from the Department for Work and Pensions annual report titled Households below Average Income) and ROI (from the Office of National Statistics Redistribution of Income analysis). We analyze overall trends in the level and distribution of household well-being using all three measures for Great Britain as a whole and for subgroups of the British population. Gains in household economic well-being between 1995 and 2005 vary by the measure used, from 23 percent (HBAI) to 32 percent (LIMEW) and 35 percent (ROI). LIMEW shows that much of the middle class's gain in well-being was as a result of increases in government expenditures. LIMEW also marks a greater increase in economic well-being among elderly households due to the increase in their net worth. The redistributive effect of net government expenditures decreased notably between 1995 and 2005 according to the official measures, primarily due to the change in the distributive impact of government expenditures.
Keywords: D31; D63; P17; 330; Levy Institute Measure of Economic Well-being (LIMEW); Great Britain; economic well-being; economic inequality; household income measures; Lebensstandard; Haushaltseinkommen; Messung; Soziale Schicht; Großbritannien